Public Health And Nursing: Bridging Care And Community Well-Being (The Review of Diabetic Studies, 2024)
Background: Nursing and public health are related professions that are essential to fostering and preserving community well-being. Nursing prioritizes patient care and customized health promotion, whereas public health concentrates on disease prevention and population health improvement. When combined, they provide a thorough strategy for tackling health issues, especially in marginalized areas. The ability to manage population-level health issues while providing excellent patient care is improved when public health ideas are included into nursing practice.Aim: The purpose of this conversation is to examine the ways in which public health and nursing might work together to improve community health. It aims to show how public health-informed nursing practices may effectively address new health issues, lessen health inequalities, and advance fair access to care. Finding methods for enabling nurses to take the lead in public health campaigns is another goal.Conclusion: To address the complex health needs of communities, nursing practice must incorporate public health principles. As frontline healthcare professionals, nurses are in a unique position to carry out community-based health programs, advocate for disadvantaged groups, and execute public health measures. We can improve population health outcomes and create a more equitable healthcare system by encouraging cooperation across the public health and nursing domains. In the end, this alignment guarantees a comprehensive approach to health by fusing patient-centered, compassionate care with preventative measures.